(untitled) (Ius Novum, 2019)
In the current legal status, an intestate heir may conclude a contract with the person from whom he/she is to succeed, to waive succession to that person. It has the effect of treating the waiving person as if he/she did not live to the opening of the succession. However, the same treatment is also given to descendants of the person waiving succession, even though they are not parties to the contract. The issue of the need to obtain consent from a guardianship court to the waiver of succession, the effects of which also extend to minor children of the one who has waived the succession, has not been regulated. However, the de lege lata prevailing opinion is that such a consent is not required. Still, given that the effects of the waiver of succession covering a minor child are identical to the effects of rejecting the succession on behalf of a minor child (in both cases considered as not having lived to the opening of the succession), it seems appropriate to introduce into the legal system an obligation to obtain the consent of the guardianship court also to conclude a contract of waiving succession if its effects are extended to minors of the waiving person. The reason for this is the protection of the best interests of the child, who as a result of a contract of waiving succession entered into by his/her parent may, in some cases, be even totally deprived of any rights under the inheritance law which would be applicable to him/her if the waiver of succession were not concluded.